Rotation Invariant Vortices for Flow Visualization - Günther, Tobias; Schulze, Maik; Theisel, Holger (IEEE Transactions on Visualization and Computer Graphics, 2016)
We propose a new class of vortex definitions for flows that are induced by rotating mechanical parts, such as stirring devices, helicopters, hydrocyclones, centrifugal pumps, or ventilators. Instead of a Galilean invariance, we enforce a rotation invariance, i.e., the invariance of a vortex under a uniform-speed rotation of the underlying coordinate system around a fixed axis. We provide a general approach to transform a Galilean invariant vortex concept to a rotation invariant one by simply adding a closed form matrix to the Jacobian. In particular, we present rotation invariant versions of the well-known Sujudi-Haimes, Lambda-2, and Q vortex criteria. We apply them to a number of artificial and real rotating flows, showing that for these cases rotation invariant vortices give better results than their Galilean invariant counterparts.
CRIS-Team Scopus Importer:2020-09-23
Keywords: Eigenvalues and eigenfunctions; Jacobian matrices; Observers; Propellers; Rotation measurement; Transforms; Visualization